Cross-Borehole DC Resistivity Tomography of Sea Ice: Temporal and Spatial Variations in the Anisotropic Microstructure - Jones, Keleigh Ann (11677534) (2011)
As an inhomogeneous mixture of pure ice, brine, air and solid salts the physical properties of sea ice depend on its highly temperature-dependent microstructure. Understanding the microstructure and the way it responds to variations in temperature and salinity is crucial in developing an improved understanding of the interaction between sea ice and the environment. However, measurements monitoring the microstructure of sea ice are difficult to obtain without disturbing its natural state. The brine fraction of sea ice is orders of magnitude more conductive than the solid ice, thus direct current resistivity techniques should yield information on sea ice microstructure. Due to the preferential vertical alignment of brine inclusions, the bulk resistivity of first-year sea ice is anisotropic, complicating interpretation of surface resistivity soundings. However, it can be shown that in a bounded anisotropic medium the resistivity structure may be resolved through in situ cross-borehole measurements. Measurement between borehole pairs, each containing one current and one potential electrode, allows the determination of the horizontal component of the anisotropic bulk resistivity (PH). Using three to four electrodes positioned at approximately the same depth in separate boreholes, provides an under-estimation of the geometric mean resistivity (Pm), and numerical modelling is required to retrieve an estimate of the true Pm. Combining these resistivities allows calculation of the vertical component of the bulk resistivity (PV). This thesis looks at results from measurements made in first year sea ice in April – June 2008 off Barrow, Alaska and in November 2009 off Ross Island, Antarctica. At Barrow, relatively quiescent conditions typically lead to a predominance of columnar ice, while more turbulent conditions and underwater ice formation in McMurdo Sound tend to produce a larger component of frazil or platelet ice. Interpretation of the resistivity measurements, aided by temperature and salinity data, shows that this measurement technique can be used to observe evolution of the ice structure, and distinguish different ice types. Basic two phase structures provide a simple picture of the brine microstructure and how it changes with depth and time. These models indicate the need for vertical connectivity of the brine inclusions even in cool ice, and that PH seems to be mostly due to connections along grain boundaries.